Red Flags, Red Herrings, and Common Ground: An Expert Study in Response to State Reading Policy - Vicki S. Collet; Jennifer Penaflorida; Seth French; Jonathan Allred; Angelia Greiner; Jingshu Chen (Educational Considerations, 2021)
In many U.S. states, legislation seeks to define effective instruction for beginning readers, creating an urgent need to turn to scholars who are knowledgeable about ongoing reading research. This mixed-methods study considers the extent to which recognized literacy experts agreed with recommendations about instruction that were included on a state’s reading initiative website. Our purpose was to guide implementation and inform policy-makers. In alignment with the initiative, experts agreed reading aloud, comprehension, vocabulary, fluency, phonological awareness, and phonics all deserve a place in early literacy instruction. Additionally, they agreed some components not included on the website warranted attention, such as motivation, oral language, reading volume, writing, and needs-based instruction. Further, experts cautioned against extremes in describing aspects of early reading instruction. Findings suggest that experts’ knowledge of the vast body of ongoing research about reading can be a helpful guide to policy formation and implementation.
Keywords: Emergent Literacy; Instructional Strategies; Literacy Acquisition; Educational Policy